Protection measures according to the history of infection by SARS-CoV-2 in obstetricians of the Sergio E. Bernales National Hospital, 2021 - Arotoma, Nahomy Lucía (2021)
Introduction: The World Health Organization declared the SARS-CoV-2 infection a Pandemic on March 11, it expanded and arrived in Peru showing the harsh reality in the health field, leaving Health professionals vulnerable. This is why identifying protection measures and comparing them in Obstetricians with or without previous infection is of utmost importance to reduce the probability of infection in this population group. Objective: To compare the protection measures according to the history of infection by SARS-CoV-2 in obstetricians at the Sergio E. Bernales National Hospital. Materials and Methods: Non-experimental, analytical, prospective and cross-sectional study, developed in 45 obstetricians with and without a history of Covid-19. Information was collected with the survey technique with a valid instrument (in content and construct). The statistical package IBM SPSS version 25 was used for its processing, descriptive statistics were estimated for qualitative variables, to establish the relationship of variables, it was calculated with linear by linear association and Fisher's exact test. Results: The average age was 44.3 years and 100% female. In addition, 81% with previous infection, indicated that they always perform hand hygiene before contact with the patient, and in addition, 66.7% obstetricians without previous infection, most of them comply with the 12 steps for hand washing. times. Also, 71.4% of obstetricians with previous SARS-CoV-2 infection maintain a distance of 1.5m with health personnel most of the time. 47.6% of obstetricians with the infection, indicated that they have training for the care of COVID-19 patients most of the time, also that 76.2% said that they always eat well. 91.6% of those without previous infection, indicated that they did not have shifts longer than 12 hours, while 57.1% of those who did have this infection, indicated that they have not reduced the time of care with their patients. Conclusions: There were no significant differences in the protection measures adopted by obstetrician professionals with and without a history of SARS-CoV-2 infection.